Real time system on chip based wearable cardiac activity monitoring sensor - Aryan Jain; Mandeep Singh; Balwinder Singh (Measurement: Sensors, 2022)
In this research, a real time low power wearable cardiac activity monitoring device is introduced to display real time electrocardiography (ECG) signal and heart rate (HR). ECG records heart’s electrical activity and heart rate measures the contraction of the heart. The developed device consumes very less power as SoC used in this research has power consumption of 85 μW at 1.1V supply voltage. To measure heart rate and ECG waveform, the pre-gelled ECG electrodes are attached on the RA, LA and LL positon of the human’s body. These pre-gelled ECG electrodes attached to the ECG lead which is further connected to the ECG device. The ECG system is validated and the measured average HR of the subject was 71 to 82 beats per minute (BPM) and ECG graph was also plotted.